Farmers’ Behavior in White Pepper Production in Delas Village, Airgegas District, South Bangka Regency - Milonda Milonda; Evahelda Evahelda; Muntoro Muntoro (Journal of Global Sustainable Agriculture, 2023)
The decline in the amount of pepper production in Bangka Belitung was caused by the decline in the selling price of white pepper received by farmers. Apart from the decline in the selling price of white pepper, the development of other plantation commodities also influences farmers' behavior in cultivating white pepper, so that many pepper farmers choose to switch to farming other commodities. The aims of this research are 1) to describe farmers' behavior in cultivating white pepper in Delas Village, Airgegas District, South Bangka Regency, and 2) to analyze the factors that influence farmers' decisions in cultivating white pepper in Delas Village, Airgegas District, South Bangka Regency. . This research was conducted using a survey method. Sampling used purportive sampling with a sample size of 80 respondents. Data were analyzed using quantitative descriptive and binary logistic regression. The results of the research show that the behavior of farmers in cultivating white pepper in Delas Village with a percentage of 30 percent is still cultivating pepper even though the price of white pepper is low for the reason that it has been a culture passed down from generation to generation and so that the availability of pepper remains even in smaller quantities. Meanwhile, 70 percent of farmers chose to change their pepper farming to other commodities such as palm oil and rubber. The factors that influence farmers' decisions in cultivating white pepper are the variables Number of Dependents and other sources of income.